Habronematidosis in Equids: Current Status, Advances, Future Challenges - Barlaam, Alessandra; Traversa, Donato; Papini, Roberto; Giangaspero, Annunziata (Frontiers in Veterinary Science, 2020)
Over the past few decades, among equine parasitoses caused by gastrointestinal nematodes (GINs), habronemosis has been discontinuously studied worldwide. Habronemosis is a widespread parasitic disease caused by the nematodes Habronema microstoma, Habronema muscae and Draschia megastoma (Spirurida, Habronematidae), requiring muscid flies as intermediate hosts. Adults and larvae live in the stomach of horses and other equids. However, the larvae can also be found on the skin, causing lesions known as "summer sores", and occasionally on other sites, such as ocular and genital mucosa and lung parenchyma, causing muco-cutaneous habronemosis. Depending on the parasite's developmental stage and localization, clinical signs may range from mild to severe. Habronemosis is responsible for severe economic losses, mostly when sport horses are affected, because their performances are impaired and the infection can be unaesthetic. Three electronic databases were used for finding the publications on habronemosis that met the selected inclusion criteria for the systematic review and a total of 250 contributions, published between 1911 and 2020 were analyzed. This mini-review summarizes the key features of pathogenesis, epizootiology, diagnosis, treatment, and control of this parasitosis, and explores what it is currently known about its prevalence and geographical distribution. The use of anthelmintic drugs remains the most widelyused strategy for controlling habronemosis; given the known risk of anthelmintic resistance in some nematodes affecting horses, this aspect should also be explored for habronemosis. Focused research is required to fill existing gaps of knowledge to maximize equine health, reduce economic losses and sanitary impact associated with this parasitic infection.